Performance Assessment in STEM Projects: Publication Trends - Annisa Salsabila; Nurul Fitriyah Sulaeman; Zulkarnaen Zulkarnaen; Abdul Hakim (Jurnal Materi dan Pembelajaran Fisika, 2025)
In line with the global spread of Science-Technology-Engineering-Mathematics (STEM) education, increasing attention has been given to appropriate forms of assessment. Among various approaches, performance assessment is argued to be particularly suitable for evaluating STEM learning processes. This study aims to analyze publication trends and assessment approaches in performance assessment within STEM projects between 2015 and 2025. Using a Systematic Literature Review (SLR) method, 50 peer-reviewed articles retrieved from Scopus and Google Scholar were examined through thematic analysis, based on defined inclusion and exclusion criteria. The review identified key themes, methodologies, geographic distributions, and gaps in the literature. The findings reveal a significant increase in publications in 2021, reflecting growing academic interest in authentic evaluations of 21st-century skills. Authentic assessment approaches such as performance rubrics, digital portfolios, and direct observation dominate the field. Geographically, South Asia shows the highest number of publications on this topic. However, explicit theoretical integration, validation and reliability of instruments, and teacher involvement in assessment design remain limited. These findings highlight the need to strengthen theoretical foundations, participatory approaches, and methodological rigor in developing contextual and sustainable performance assessments for STEM education. By addressing these gaps, this study contributes to guiding educators, policymakers, and researchers in designing assessment practices that effectively align with the planning, implementation, and evaluation stages of STEM learning.